Strategi Kepala Sekolah dalam Menumbuhkan Religius Culture Peserta Didik di MA Muhammadiyah 02 Kabupaten Gresik - Azzahro', Adibatul Bahiroh; Rossidy, Imron (ISLAMIKA, 2024)
Religious culture is a representation of religious values which are used as traditions in behavior and culture by trying to produce students who behave well or have morals. The purpose of conducting this research is to describe and analyze the strategies of school principals as leaders of educational institutions in cultivating religious culture in students at school. Interview, observation and documentation methods were used by researchers to collect data in this research using a qualitative approach. The results of the research show that the strategy used by school principals in cultivating the religious culture of students in schools is to use habituation and exemplary strategies through several activities such as midday prayers in congregation, tadarus al-Quran, tahfidz, dhikr after prayer, 5S culture, PHBI, visiting a friend who is sick or has had an accident.